The ghosts of sherwood eaudiobook - Vaughn, Carrie (Robin Hood Duology, 2020)
Carrie Vaughn's The Ghosts of Sherwood revisits the Robin Hood legend with a story of the famed archer's children. Everything about Father is stories. Robin of Locksley and his one true love, Marian, are married. It has been close on two decades since they beat the Sheriff of Nottingham with the help of a diverse band of talented friends. King John is now on the throne, and Robin has sworn fealty in order to further protect not just his family, but those of the lords and barons who look up to him – and, by extension, the villagers they protect. There is a truce. An uneasy one, to be sure, but a truce, nonetheless. But when the Locksley children are stolen away by persons unknown, Robin and Marian are going to need the help of everyone they've ever known, perhaps even the ghosts that are said to reside deep within Sherwood. And the Locksley children, despite appearances to the contrary, are not without tricks of their own...